Tuberculosis Drug-Induced Liver Injury - Soedarsono Soedarsono; Agustinus Rizki Wirawan Riadi (Jurnal Respirasi, 2020)
Effective tuberculosis (TB) treatment requires a combination of bactericidal and/or bacteriostatic TB drugs. The combination of these regimens is the standard therapy recommended by World Health Organization (WHO). The standard therapy consists of 5 first-line anti-TB drugs (isoniazid, rifampicin, pyrazinamide, ethambutol, and streptomycin). TB drugs have mild to severe side effects. Side effects that arise not only cause mortality and morbidity but also cause the cessation of treatment with the effect of not achieving cure, even arising drug resistance. Drug-induced liver injury (DILI) is a form of side effect that causes the cessation of TB treatment or regimen changes due to treatment failure, relapse, and drug resistance. DILI increases the problem, covering more than 7% of all side effects. DILI is also one of the concerns in the treatment of TB.